2022
DOI: 10.2166/wrd.2022.095
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of an HDH desalination system using direct contact packed towers: experimental and mathematical modeling study

Abstract: Humidification–dehumidification desalination (HDH) is one of the suitable methods for desalination of saline and brackish water in a small scale. In this research, a HDH desalination method with a direct contact dehumidifier has been analyzed theoretically and experimentally. The setup consists of two similar packing towers for humidification and dehumidification, 10 inches in diameter, which are filled up to 1 m with Rushing packing. In this new HDH configuration, seawater and freshwater recirculation has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…m da (h a,2 − h a,1 ) = m fw,o h fw,2 − m fw,i h fw,1 (19) where m fw,i and h fw,1 are mass flow rate and specific enthalpy of freshwater at the inlet of dehumidifier; m fw,o and h fw,2 represent the mass flow rate and specific enthalpy of freshwater at the outlet of dehumidifier; m pw refers to water production during the condensation process.…”
Section: Model Of Packed Bed Humidifier and Dehumidifiermentioning
confidence: 99%
See 1 more Smart Citation
“…m da (h a,2 − h a,1 ) = m fw,o h fw,2 − m fw,i h fw,1 (19) where m fw,i and h fw,1 are mass flow rate and specific enthalpy of freshwater at the inlet of dehumidifier; m fw,o and h fw,2 represent the mass flow rate and specific enthalpy of freshwater at the outlet of dehumidifier; m pw refers to water production during the condensation process.…”
Section: Model Of Packed Bed Humidifier and Dehumidifiermentioning
confidence: 99%
“…The research results showed that the maximum value of net power and water production were 42.68 kW and 236.81 kgh −1 , respectively. Considering the recirculation of seawater and freshwater, Zarei et al [19] raised a CACW HDH desalination system with a directcontact humidifier and dehumidifier. The relevant theoretical and experimental analyses were conducted at the various input parameter conditions, and the results showed that the peak value of GOR and water production are 3.3 and 300 Ld −1 at the equilibrium conditions of the dehumidifier.…”
Section: Introductionmentioning
confidence: 99%